FOREIGN LANGUAGE TRAINING OF MASTER’S DEGREE STUDENTS OF TECHNICAL SPECIALTIES (EDUCATION IN THE 21ST CENTURY, 2024)
The purpose of the study is to characterize the peculiarities of foreign language training of master’s degree students of technical specialties based on the analysis of modern research.The relevance of the raised problem is determined by the fact that the modernization of higher education, its entry into the European and world educational space is not possible without a significant increase in the quality of foreign language training of master’s degree students, in particular, technical specialities.The novelty of the research lies in the fact that the article characterises features of foreign language training of master’s degree students of technical specialties, namely: admission based on the Unified Entrance Exam in foreign languages taking into account the Common European Framework of Reference for Languages: Learning, Teaching, Assessment in order to balance the level of language proficiency of students (level B1-B2); availability of a wide range of disciplines for foreign language training of master’s degree students, in particular: "Practical Foreign Language Course for Business Communication (English)", "Practical Foreign Language Course for Scientific Communication (English)", "Universal Competencies for Career Success", "English for Scientific Communication", "Ethics of Business and Professional Communication", "Business Foreign Language", "English for Specific Purposes", "Foreign language (English) for Scientific Publications", "Scientific Foreign Language" and others; strengthening the practical component of foreign language training of master’s degree students of technical specialties; continuity of foreign language education of master’s degree students of technical specialties; partial involvement in master's programs the Content and Language Integrated Learning, which is based on the study of professional disciplines in inseparable unity with foreign language mastering, the involvement of intra-disciplinary and interdisciplinary connections; increasing motivation both for the foreign language learning and profession; expanding opportunities for lifelong learning, continuous self-improvement and self-development; study of professional disciplines in foreign languages.Conclusions. As a result of the conducted research, the peculiarities of foreign language training of master’s degree students of technical specialties have been characterised. The material and conclusions of the research can be used to modernize the educational process of foreign language training of master’s degree students of technical profiles, improve curricula and programs. It is found that further scientific research can be devoted to the study of innovative methods and approaches to the foreign language training of master’s degree students of technical specialties.
Keywords: foreign language training; master’s degree students of technical specialties; Common European Framework of Reference for Languages; the Content and Language Integrated Learning